Toward Improving General Quantum Imaging Algorithms and the Realization of Quantum Recording - Freitas, Brayden (Université d'Ottawa | University of Ottawa, 2025)
Various quantum imaging techniques have been shown to be effective at imaging through some aspects of traditionally difficult free-space channels, including ghost imaging through turbulent channels, or quantum illumination through channels with noisy backgrounds. For quantum illumination through channels with noisy background, a full rigorous theoretical framework has never been given. This thesis begins by providing such a theoretical framework for a version of quantum illumination which relies on spatial correlations. While these techniques have only ever been shown to work independently, real-world free-space channels are often both turbulent and noisy simultaneously. This thesis then goes on to describe and experimentally demonstrate a quantum correlated imaging method which uses an SPDC source and a time-tagging camera which be made robust against both turbulent media and a noisy background in free-space channels by implementing filtering based on the temporal and spatial correlations of paired photons. Furthermore, the filtering reduces accidental coincidence counts between uncorrelated photons, allowing the pair source to operate at high brightness which, in turn, leads to video-rate integration times. These quantum correlated recordings allow for improved object tracking, while the longer integration time images improve image fidelity over turbulent and noisy channels. This demonstration could allow for new improvements in communication, measurement, and sensing through turbulent and noisy free-space channels.
Keywords: quantum; optics; imaging; lidar